The Complexity of Sentence Structure on English Texts Developed by Indonesian Students - Faroha, Ulya; Asmiyah, Siti; Nafidah, Hikmah (ICONELT, 2024)
Complexity of sentence structure may depend on the type of text being developed. This research explored the sentence structure on English procedural text made by the Indonesian students, with focus on investigating common sentence types also as the error on students’ writings. This research took the work of students at a public senior high school in Sidoarjo as the source of data. It reveals that the common sentences used by the students are simple sentences with a total of 70% of the texts. High preference on simple sentence structure shows a good understanding of procedural text, which prioritizes clarity and directness for making instructions that are easy to follow for the readers. In addition, the research also indicates few grammatical errors on verb tense and subject-verb agreement, but there are still some occurrences in which students’ occasionally make errors in pronoun-agreement, which suggest room for improving their English writing skills. The findings imply that balancing simple and complex sentences can help an instructional sentence become easier to understand by providing deeper information while maintaining clear instruction. Additionally, further research could explore different sentence structure and how it can be used effectively. Similar research on different genres is also worth considering.